Students’ Mathematical Critical Thinking Using Geogebra Software Based on Adversity Quotient - Fitri Alyani; Natalia Dinda Sartika Putri (Universitas Pendidikan Ganesha, 2022)
The ability to think critically is not balanced with the optimal learning approach, to the low achievement of mathematical critical thinking ability (MCTA). Quasi-experimental research with a quantitative approach was used to determine the differences in learning using GeoGebra software for the experimental and the control class on MCTA in terms of adversity quotient (AQ). Class XI high school students in one of the schools in Jakarta as the research population, with sample students of 40 from the experimental class and 40 from the control class selected purposively. The instrument is based on an assessment of MCTA and an AQ questionnaire. The Mann-Whitney U Test, Spearman Correlation, and Cohen's d Effect Size were used to analyze the data. The results show the experimental class's MCTA is better than the control class. Based on Wright Maps, the AQ of climber-type students is dominated by the experiment class, while the control class dominates the quitter. The conclusion of this study, there are differences in the MCTA of the experimental class using GeoGebra software and the control class in terms of AQ.